Facial Sadness Recognition is Modulated by Estrogen Receptor Gene Polymorphisms in Healthy Females - Gutiérrez Muñoz, Mayra; Fajardo Araujo, Martha; González Pérez, Erika; Aguirre Arzola, Víctor Eustorgio; Solís Ortiz, Silvia (Molecular Diversity Preservation International, 2018)
Abstract: Polymorphisms of the estrogen receptor ESR1 and ESR2 genes have been linked with cognitivedeﬁcitsandaffectivedisorders. Theeffectsofthesegeneticvariantsonemotionalprocessing infemaleswithlowestrogenlevelsarenotwellknown. TheaimwastoexploretheimpactoftheESR1 and ESR2 genes on the responses to the facial emotion recognition task in females. Postmenopausal healthy female volunteers were genotyped for the polymorphisms Xbal and PvuII of ESR1 and the polymorphism rs1256030 of ESR2. The effect of these polymorphisms on the response to the facial emotion recognition of the emotions happiness, sadness, disgust, anger, surprise, and fear was analyzed. Females carrying the P allele of the PvuII polymorphism or the X allele of the Xbal polymorphism of ESR1 easily recognized facial expressions of sadness that were more difﬁcult for the women carrying the p allele or the x allele. They displayed higher accuracy, fast response time, more correct responses, and fewer omissions to complete the task, with a large effect size. Women carrying the ESR2 C allele of ESR2 showed a faster response time for recognizing facial expressionsofanger. TheseﬁndingslinkESR1andESR2polymorphismsinfacialemotionrecognition of negative emotions.